PERAN KEPROTOKOLAN DALAM KEGIATAN DIPLOMATIK DITINJAU DARI HUKUM INTERNASIONAL - Hazza Azhar Arrijal; Sutiarnoto Sutiarnoto; Arif Arif (Journal of USU International Law, 2020)
ABSTRACT Hazza Azhar Arrijal* Sutiarnoto** Arif***   Protocol is a series of activities related to the rules in a state event or official event which includes the procedure for place, ceremony and respect as a form of respect for State Officials, Government Officials, representatives of foreign countries and / or international organizations, and certain community leaders based on the Act Law No. 9 of 2010 concerning Protocols. Protocols are influenced by international customs which are then standardized and enacted as a guide for behavior, especially in diplomatic relations. The aspect of international law is inherent in protocol because the parent of the protocol itself is that international custom is one source of international law, especially in diplomatic law. The role of protocol becomes an inseparable part of the success of a diplomatic activity. The formulation of the problem from the writing of this thesis is how the arrangement of diplomatic law related to protocol, how the international legal aspects of protocol, and how the role of protocol in diplomatic activities. This type of research is a normative method that is by studying the study of documents such as legislation, international treaties, judges' decisions, legal theories and scholar opinions relating to the role of protocol in diplomatic activities from an international legal perspective. Protocol rules that are applied and implemented in a diplomatic activity have a positive role which is to determine the atmosphere that influences the success of an event. Protocol also plays a role in creating social relations that bring one country closer to one another. Also important is the protocol to provide a sense of protection, order, security and comfort for all diplomatic representatives who carry out their duties.         Keywords: Role, Protocol, Diplomatic Activities